PENGARUH SELF ASSESSMENT SYSTEM DAN PEMERIKSAAN PAJAK TERHADAP PENERIMAAN PAJAK PERTAMBAHAN NILAI (Studi Empiris pada KPP Pratama Bengkalis) - Maysarah, Maysarah; Agusti, Restu; Aunurrafiq, Aunurrafiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
This study aims to examine the effect of the Self Assessment System and TaxAudit on Value Added Tax Revenue at KPP Pratama Bengkalis in 2019-2023. Theresearch method used is quantitative research with data analysis techniques usingSPSS Version 22 software. The sample in the study amounted to 60. The samplingtechnique used Purposive Sampling. The results of the study concluded that the SelfAssessment System and Tax Audit had no effect on Value Added Tax.Keyword : Self Assessemnt System,Tax Audit, and Value Added Tax (VAT)